How to Perform miRacles: A Step‐by‐Step microRNA Detection Protocol Using DNA Nanoswitches. Issue 1 (12th February 2020) - Chandrasekaran, Arun Richard; Dey, Bijan K.; Halvorsen, Ken
Abstract: MicroRNAs are short non‐coding RNAs involved in post‐transcriptional gene regulation, and are increasingly considered to be biomarkers for numerous biological processes and human diseases. Current techniques used for microRNA detection can be expensive and labor‐intensive, and typically require amplification, labeling, or radioactive probes. In this protocol, we describe a DNA nanoswitch–based microRNA detection assay termed  "miRacles": microRNA‐activated conditional looping of engineered switches. This method uses conformationally responsive DNA nanoswitches that detect the presence of specific microRNAs with a simple and unambiguous gel‐shift assay that can be performed on the benchtop. The assay is low cost, minimalistic, and capable of direct detection of specific microRNAs in unprocessed total RNA samples, with no enzymatic amplification, labeling, or special equipment. The protocol for detection of microRNAs in total RNA can be completed in as little as a few hours, making this assay a compelling alternative to qPCR and Northern blotting. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Preparation of DNA nanoswitches Basic Protocol 2 : Detection of microRNAs from total RNA samples Support Protocol 1 : Optional nanoswitch purification by PEG precipitation Support Protocol 2 : Optional nanoswitch purification by liquid chromatography